A Facile Route to Stereoselective Synthesis of Exo-4,5-epoxytricyclo[6.2.1.02,7]undeca-9-ene-3,6-diol as a Valuable Intermediate to Conduritol-F Natural Product - Mamaghani, Manouchehr; Hajsaidhady, Zahra (Asian Journal of Chemistry, 2016)
Tricyclo[6.2.1.02.7]undeca-4,9-diene-3,6-diol (2) was prepared from readily available tricyclo[6.2.1.02.7]undeca-4,9-diene-3,6-dione and was transformed in an entirely new and convenient route to exo-4,5-epoxytricyclo[6.2.1.02.7]undeca-9-ene-3,6-diol (5) as a valuable intermediate to the synthesis of conduritol-F.